Improving working memory abilities in individuals with Down syndrome: a treatment case study - Costa, Hiwet Mariam; Purser, Harry R.; Passolunghi, Maria Chiara (Frontiers in Psychology, 2015)
Working Memory (WM) skills of individuals with Down’s syndrome DS tend to be very poor compared to typically developing children of similar mental age. In particular, research has found that in individuals with DS visuo-spatial WM is better preserved than verbal WM. This study investigated whether is possible to train Short-Term Memory (STM) and WM abilities in individuals with DS. The cases of two teenage children are reported: E.H., 17 years and 3 months, and A.S., 15 years and 11 months. A school-based treatment targeting visuo-spatial WM was given to E.H. and A.S. for six weeks. Both prior to and after the treatment, they completed a set of assessments to measure WM abilities and their performance was compared with younger typically developing nonverbal mental age controls. The results showed that the trained participants improved their performance in some of the trained and non-trained WM tasks proposed, especially with regard to the tasks assessing visuo-spatial WM abilities. These findings are discussed on the basis of their theoretical, educational and clinical implications.